THE CRY OF THE EARTH: Religious Perspectives - Nandhikkara, Jose (Journal of Dharma, 2022)
The unique position of the human species lies in the contested fact that only human beings contributed to climate change and the certain fact that only they are capable of bringing positive changes. It is not only a matter of ‘can’ but also about responsibility. To this effect, only human beings can articulate an ethics of climate change and undertake obligations to act accordingly. As rational beings, we know that we are part of the problem; as moral beings, we should take responsibility for our common home and be part of the solutions. It is, therefore, a moral imperative and religious responsibility that we develop an integral ecology, bringing together all the fields of knowledge, economic, and political powers protecting and promoting the integrity of creation as an antidote to the omnipresent technocratic economic paradigm with the ‘use and throw away’ culture driven by a market economy and short-term electoral goals of politics. The economics of more is detrimental to the well-being of the Earth and the earthlings, including human beings. As moral agents, we can no longer treat the planet as a source of our consumeristic pleasure and sink for the waste we make through our unsustainable living. From a religious point of view, human beings are caretakers of the Earth and all who are living in this common home in collaboration and solidarity with all. We are responsible to God, fellow human beings and the creation. Our lives are rooted in nature, extended to the community, and guided by and oriented to God.